Structural Assessment and Rehabilitation of an Existing Hydraulic Masonry Structure Supporting Railway - Makhlouf, Aly A.; Omar, M.; Emarah, Dina A. (Civil Engineering Journal, 2025)
Old hydraulic masonry structures are essential components of global road and rail infrastructures. Over decades of operation, these structures have experienced inevitable deterioration, necessitating evaluations of their structural conditions through comprehensive assessment and rehabilitation programs to ensure compliance with contemporary safety standards. This study focuses on a specific regulator as a case example to implement a rehabilitation strategy aimed at restoring its structural integrity after 190 years of continuous service. From 2015 to 2021, an extensive program was conducted to assess the condition of the construction materials. This program included mechanical and physical testing, as well as Finite Element Analysis (FEA), to identify areas of high stress and to analyze the distribution of stress throughout the structure. The findings revealed that the structure fails to meet current Egyptian standards, thereby underscoring the critical need for a strengthening program. Subsequently, a rehabilitation intervention was developed, which involved reinforcing the intrados of the arches and piers with a slender reinforced concrete jacket. These reinforcements were integrated with the existing structure using steel shear bar connectors. Following the rehabilitation, a re-evaluation of the analysis of the modified structure using FEA software confirmed compliance with Egyptian specifications. The proposed rehabilitation strategy offers a viable solution to the challenges associated with the examined masonry arch bridge. Doi: 10.28991/CEJ-2025-011-02-012 Full Text: PDF